Drawbridges Down: Altruism and Immigration Preferences - Ole-Petter Moe Hansen; Stefan Legge (Center for Economic Studies and ifo Institute (CESifo), 2016)
This paper advances and empirically establishes the idea that altruism is an important determinant of individual preferences over immigration. Using data from the European Social Survey from 2014 and 2015, our results document that individual norms and values strongly shape preferences over immigration, even when controlling for expected costs and benefits from immigration. In particular, we find that altruistic attitudes significantly raise the support for all types of immigration while xenophobic views lower the support. A newly developed latent-factor model allows us to quantify and compare the relative importance of each determinant of immigration policy preferences.
Keywords: F22; H20; O15; 330; altruism; Europe; immigration; racism; xenophobia